A construção da marca país: uma proposta de comunicação educativa - Preto, Vitor Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This monograph presents the main results of the research that had as objectives: 1) to characterize the communication role in the construction of national campaigns denominated country-brand; and 2) promote reflection on the themes of building cultural identity and representation of the Brazil brand, through educational communication. The research methodology involved exploratory work on the strategy adopted by countries to establish themselves as brands and the attribution of communication in this process of market positioning. In addition, data collection during the research and the objective of promoting reflection allowed the elaboration and application of an online and face-to-face course that relates the phenomenon of Globalization to the present competitive scenario that obliges countries to create and position themselves as brands. The main result produced by the research was the reflection on the representativeness of the Brazilian brand, under the influence of globalization and internal political processes. In this way, the communication fulfilled its educational role of providing the reflection of students about the representativeness of the Brazil brand

A presente monografia apresenta os principais resultados da pesquisa que teve como objetivos: 1) caracterizar o papel da comunicação na construção de campanhas nacionais denominadas marca-país; e 2) promover a reflexão sobre os temas de construção de identidade cultural e representação da marca Brasil, por meio da comunicação educativa. A metodologia da pesquisa contou com um trabalho de natureza exploratória sobre a estratégia adotada por países de se colocarem como marcas e a atribuição da comunicação nesse processo de posicionamento no mercado. Além disso, o levantamento dos dados durante a pesquisa e o objetivo de promover a reflexão possibilitaram a elaboração e aplicação de um curso online e presencial que relaciona o fenômeno da Globalização com o presente cenário competitivo que obriga países a criarem e se posicionarem como marcas. O principal resultado produzido pela pesquisa foi a reflexão sobre a representatividade da marca brasileira, sob a influência da globalização e de processos políticos internos. Desta forma, a comunicação cumpriu seu papel educativo de proporcionar a reflexão de alunos sobre a representatividade da marca Brasil
Keywords: Comunicação; Globalização; Política de comunicação; Communication